1997
DOI: 10.1007/bf00788519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ischemia, preconditioning, and adenosine deaminase inhibition on interstitial adenosine levels and infarct size

Abstract: In order to examine the relationship between local adenosine concentrations before, during, and after ischemia and the extent of ischemic myocardial damage, measurements of interstitial fluid (ISF) nucleosides were made using microdialysis probes implanted in the ischemic region of isoflurane anesthetized Micropigs undergoing 60' coronary artery occlusion (CAO) and 3 h of reperfusion (REP). Nucleoside concentrations in the dialysate collected from the microdialysis probes were used as an index of ISF levels. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The effects of Ado on vasculature, as demonstrated in this study, may play a role in post-ischaemic situations or after transient hypoxia. Increase in Ado concentrations in the micromolar range has been described in several studies in the kidney and heart (Martin et al 1997, Kloor et al 2002. The results of our study suggest an Ado uptake into cells, when extracellular concentrations are higher than 10 )6 mol L )1 , i.e.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The effects of Ado on vasculature, as demonstrated in this study, may play a role in post-ischaemic situations or after transient hypoxia. Increase in Ado concentrations in the micromolar range has been described in several studies in the kidney and heart (Martin et al 1997, Kloor et al 2002. The results of our study suggest an Ado uptake into cells, when extracellular concentrations are higher than 10 )6 mol L )1 , i.e.…”
Section: Discussionsupporting
confidence: 78%
“…Increase in Ado concentrations in the micromolar range has been described in several studies in the kidney and heart (Martin et al 1997, Kloor et al 2002. Increase in Ado concentrations in the micromolar range has been described in several studies in the kidney and heart (Martin et al 1997, Kloor et al 2002.…”
Section: Discussionmentioning
confidence: 90%
“…One hypothesis suggested that preconditioning is protective by increasing tissue adenosine levels through activation of ecto‐5â€Č‐nucleotidase (Kitakaze et al ., ). However, measurements of myocardial adenosine levels revealed that tissue adenosine concentration actually falls in IPC hearts (Goto et al ., ; Martin et al ., ). Our studies have indicated that the initial step of the mediator phase is activation of adenosine A 2B receptors (Philipp et al ., ).…”
Section: The Mediator Phasementioning
confidence: 97%
“…Concentrations of extracellular adenosine were demonstrated to increase in ischemic hearts, where it becomes a part of the pathological environment (Martin et al, 1997;Willems et al, 2006). Adenosine exerts its actions via cell surface receptors of the G protein-coupled receptor family, namely A 1 , A 2A , A 2B , and A 3 (Fredholm et al, 2001).…”
Section: Introductionmentioning
confidence: 99%